Pencil painting like preparation for flexible thermoelectric material of high-performance p-type Na1.4Co2O4 and novel n-type NaxCo2O4 - Zhen Tian; Jun Wang; Xinba Yaer; Hui-Jun Kang; Xiao-Huan Wang; Hui-Min Liu; De-zhi Yang; Tong-Min Wang (Journal of Materiomics, 2021)
Flexible thermoelectric materials are presented with potential applications in electronic devices and energy conversion due to their convenient preparation, good flexibility, and various forms. However, as ductility is rarely observed in inorganic semiconductors and ceramic insulators, reports on applications of inorganic oxide materials in flexible thermoelectric materials are sparse. Here, we report a new method for the synthesis of a flexible Na1.4Co2O4 thermoelectric material based on Na1.4Co2O4 bulk materials, which are prepared by a self-flux method and painted on print paper. Seebeck coefficient and power factor of the obtained thermoelectric material are 78–102 μVK-1 and 159–223 μWm−1K−2, respectively, in a temperature range of 303–522 K, which are superior to those values of other conductive polymers and their compounds. More interestingly, the n-type Na1.4Co2O4 flexible material is obtained in the painting process at higher pressure with Seebeck coefficients of −109 to −183 μVK−1 in a temperature range of 303–522 K. The convenient preparation method of these novel flexible thermoelectric materials may be expanded to the synthesis of other flexible thermoelectric materials, which will be the focus of future work.